Formation initiale à l’enseignement : un carnet d’apprentissage inspiré par Gandhi - Sandrine Breithaupt; Nicole Goetschi Danesi; Nadia Lausselet; Jessy Piguet (Éducation et Socialisation)
Gandhi and Naï Talim: What legacy for teacher training? This article proposes a qualitative analysis of "learning notebooks", used as a training tool in an international module conducted between the HEP Vaud, the University of New Delhi and a school in Maharashtra. The analysis identified five main categories of content present in the notebooks. It also reveals enunciative processes of juxtaposition and articulation, but not integration. We can thus question the contributions of the module as well as our research practices.